HUBUNGAN TINGKAT PENGETAHUAN TENTANG DIABETES MELLITUS DENGAN PERILAKU MENGONTROL GULA DARAH PADA PASIEN RAWAT JALAN DI PUSKESMAS KAUMAN KABUPATEN TULUNGAGUNG - Eny masruroh; Aesthetica Islamy (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2022)
Diabetes mellitus (DM) is a chronic disease that requires long-term health care. Understanding the disease is very important in efforts to control disease behavior so that patients can live longer with a good quality of life. This study aims to determine the relationship between knowledge about DM and behavior to control blood sugarThe type of research is correlational analytic with a cross sectional approach. The research instrument was in the form of a questionnaire. The population is DM patients at the Kauman Public Health Center, Tulungagung Regency. Samples were taken by purposive sampling technique of 30 respondents. Data were analyzed by Spearman Rho test. The results showed that (50%) of respondents had knowledge in the good category, and (60%) of respondents had good behavior about controlling blood sugar. Spearman Rho statistical test results obtained P Value = 0.000 <0.05 so H1 is accepted, which means that there is a relationship between Knowledge about DM and Blood Sugar Control Behavior. It can be concluded that the knowledge of DM patients about the disease is very influential on behavior in controlling blood sugar so that health promotion efforts must continue to be improved in order to maintain health and quality of life.